Peripartum access to care in Mozambique: Opportunities for reducing maternal mortality - Mocumbi, Ana; Jacinto, Elsa; Mocumbi, Sibone (SA Heart Journal, 2022)
Women's health is prioritised in national health policies and strategies in Mozambique. However, only 34.1% of women start antenatal consultations before the 16th gestational week and attend at least 4 visits – the reported lack of easy access to health facilities contributing to late initiation of antenatal care. Data from the Mozambique National Audit Committee of maternal, perinatal, and neonatal deaths demonstrate institutional maternal mortality ratio increased from 81 deaths per 100 000 live births in 2016 to 84 in 2019, highlighting the need for greater surveillance and a vigorous response to this increase. In Mozambique, there are opportunities for improving access to and quality of peripartum care to reduce maternal morbidity and mortality. Research is needed to uncover the major causes of maternal mortality and morbidity, particularly the role of cardiovascular disease.